Fatal Paraneoplastic Embolisms in Both Circulations in a Patient with Poorly Differentiated Neuroendocrine Tumour. (30th December 2013) - Busch, A.; Tschernitz, S.; Thurner, A.; Kellersmann, R.; Lorenz, U.
Abstract : Arterial embolism with lower limb ischemia is a rare manifestation of paraneoplastic hypercoagulability in cancer patients. We report a unique case of fatal thromboembolism involving both circulations associated with a poorly differentiated neuroendocrine tumor of the lung with rapid progress despite high doses of unfractioned heparin and review the current literature on anticoagulative regimen in tumour patients.